The Performance Comparison of Several Defrosting Modes for Air-source Heat Pump - Zhang Jie; Lan Jing; Du Ruihuan; Gao Guofeng (Zhileng xuebao)
The defrosting time, discharge pressure, indoor temperature fluctuations and other defrosting characteristics of air source heat pump were experimentally investigated at three defrosting modes, i.e., reverse cycle defrosting, hot gas bypass defrosting and phase change material defrosting. The results showed that the performance of phase change material defrosting system is better than the others. The phase change material has increased the discharge temperature and the condensing temperature, which benefits to the decrease of defrost time and energy consumption, and the indoor temperature is relatively stable.